Tourism in Northeastern Argentina : the Intersection of Human and Indigenous Rights with the Environment. - Seymoure, Penny (Lexington Books, 2011)
Using the rubrics of individual, Indigenous, and environmental rights, Tourism in Northeastern Argentina: The Intersection of Human and Indigenous Rights with the Environment, edited by Penny Seymoure and Jeffrey L. Roberg, utilizes in-depth case studies developed from field work to explore the physical and psychological impact of tourism on local communities, Indigenous cultures, and the environment in northeastern Argentina. The case studies demonstrate the effects of tourism on sever.